2011 International Reliability Physics Symposium 2011
DOI: 10.1109/irps.2011.5784492
|View full text |Cite
|
Sign up to set email alerts
|

Formation of highly reliable Cu/low-k interconnects by using CVD Co barrier in dual damascene structures

Abstract: CVD Co film was investigated as an alternative barrier layer to the conventional PVD TaN\Ta in V1\M2 structure for 32nm node. We improved via filling performance and upstream (V1→M2) electromigration (EM) lifetime by more than three times. Excellent step coverage of CVD barrier makes it possible to reduce the thickness of the barrier metal by 30% and to increase the volume of Cu in metal lines. RC delay also reduced with decrease in resistance. Since adhesion at the interface between the barrier-Co and Cu also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…11,12 Thus, a sidewall material is required in which the adhesion strength is not affected by impurities. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The relationship between the adhesion strength and interfacial energy can be expressed by the Young-Dupre equation. The lower interfacial energy between two materials produces high adhesion strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Thus, a sidewall material is required in which the adhesion strength is not affected by impurities. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The relationship between the adhesion strength and interfacial energy can be expressed by the Young-Dupre equation. The lower interfacial energy between two materials produces high adhesion strength.…”
mentioning
confidence: 99%
“…[13][14][15] Due to their lattice constants, Ru (hcp), Os (hcp), and Co (fcc/hcp) have an advantage in their adhesion with Cu. 15 More recent studies have demonstrated an enhanced EM lifetime using either a CVD-Co liner or CVD-Ru liner z E-mail: Hideharu.Shimizu@tn-sanso.co.jp in interconnects, compared with those that use PVD-Ta; [13][14][15][16][17][18][19][20] in these studies, however, PVD-TaN was used as the barrier metal.…”
mentioning
confidence: 99%
“…11,12 Therefore, for the sidewall, other materials, in which adhesion strength is not affected by impurities, must be developed. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] From the viewpoint of surface engineering, Young-Dupre's equation expresses the relationship between adhesion strength and interfacial energy. Lower interfacial energy between two materials produces high adhesion strength.…”
mentioning
confidence: 99%
“…15 Some studies have recently resulted in enhanced EM lifetime using either a CVD-Co liner or CVD-Ru liner in Cu-interconnects z E-mail: Hideharu.Shimizu@tn-sanso.co.jp instead of using PVD-Ta. [13][14][15][16][17][18][19][20] However, in those studies, PVD-TaN was still used as the barrier metal.…”
mentioning
confidence: 99%
“…Cobalt is used in a wide variety of technological applications: with a higher sticking coefficient toward copper, cobalt has been used to replace tantalum as a lining material within interconnect trenches in microelectronic devices. , The cobalt layer allows for better copper seed layer coverage thereby reducing copper agglomeration and void formation . Thin films of cobalt, which are ferromagnetic, may be layered with nonmagnetic metals to form devices that take advantage of giant magnetoresistance. , These devices can be used in magnetic data storage media.…”
Section: Introductionmentioning
confidence: 99%